MANAGERIAL OWNERSHIP, DIVIDEND POLICY, AND INTELLECTUAL CAPITAL ON CORPORATE VALUES WITH PROFITABILITY AS AN INTERVENING VARIABLE : AN EVIDENCE OF REAL ESTATE AND PROPERTY COMPANIES IN INDONESIA STOCK EXCHANGE - Harlyn Lindon Siagian (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2020)
This study aims to determine Managerial Ownership, Dividend Policy and Intellectual Capital Policy on Corporate Value with Profitability as an intervening variable in real estate and property companies listed in the Indonesia Stock Exchange in 2012-2018. This type of research is causal associative. The sampling technique uses purposive sampling. Data on research were 6 companies was obtained so that the research data were 42. The analysis technique used was multiple regression and path analysis. The results of this study indicate that Dividend Policy affect Profitability, Managerial Ownership does not affects to Profitability and Intellectual Capital does not affect Profitability. Further, Managerial Ownership, Return on Assets, and Intellectual Capital does not affects the Value of the Company, Dividend Policy effect the Company Value. Profitability is an intervening variable between Dividend Policy on Firm Value, Profitability is not an intervening variable between Managerial Ownership of Company Value and Profitability is not an intervening variable between Intellectual Capital.